Probiotics Regulate Gut Microbiota: An Effective Method to Improve Immunity - Wang, Xinzhou; Zhang, Peng; Zhang, Xin (Molecules (Basel, Switzerland), 2021)
Probiotics are beneficial active microorganisms that colonize the human intestines and change the composition of the flora in particular parts of the host. Recently, the use of probiotics to regulate intestinal flora to improve host immunity has received widespread attention. Recent evidence has shown that probiotics play significant roles in gut microbiota composition, which can inhibit the colonization of pathogenic bacteria in the intestine, help the host build a healthy intestinal mucosa protective layer, and enhance the host immune system. Based on the close relationship between the gut microbiota and human immunity, it has become an extremely effective way to improve human immunity by regulating the gut microbiome with probiotics. In this review, we discussed the influence of probiotics on the gut microbiota and human immunity, and the relationship between immunity, probiotics, gut microbiota, and life quality. We further emphasized the regulation of gut microflora through probiotics, thereby enhancing human immunity and improving people’s lives.